2022
DOI: 10.11594/ijmaber.03.03.12
|View full text |Cite
|
Sign up to set email alerts
|

Tracer Study of Teacher Education Graduates of Western Philippines University - Puerto Princesa Campus: Basis for Curriculum Review and Revision

Abstract: Graduates' employability indicates the excellent education and relevant preparation they obtained from their respective degrees. Tracer studies have enabled higher education institutions to profile their graduates while also reflecting on the quality of education they provide. With the foregoing, a tracer study determined the demographic and academic profile of teacher education graduates from 2017 to 2020 in a state university in the West Philippines. It also ascertained the advanced studies they attended aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 14 publications
(56 reference statements)
3
17
0
Order By: Relevance
“…Tracer studies of Cornillez et al (2021) and Oboza (2017) revealed that the primary reason of teacher education graduates in pursuing teacher education degrees in college was the influence from their parents and/or relatives who convinced them to choose the programs for they were likely to be employed in the job market after earning their teacher education degrees in college. However, a different result was found in the tracer study of Pentang et al (2022) where it was revealed that the graduates' strong passion for the teaching profession was their main reason for earning teacher education degrees in college.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…Tracer studies of Cornillez et al (2021) and Oboza (2017) revealed that the primary reason of teacher education graduates in pursuing teacher education degrees in college was the influence from their parents and/or relatives who convinced them to choose the programs for they were likely to be employed in the job market after earning their teacher education degrees in college. However, a different result was found in the tracer study of Pentang et al (2022) where it was revealed that the graduates' strong passion for the teaching profession was their main reason for earning teacher education degrees in college.…”
Section: Introductionmentioning
confidence: 81%
“…However, a different result was showed in the study conducted by Oboza (2017) where most of them were employed with contractual status. Also, Cornillez et al (2021), Oboza (2017), Tican (2016), Pentang et al (2022), Abana et al (2021), Biscante et al (2019), and Abas et al (2020 showed that only some of the graduates were unemployed and most were employed in the job market.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the ratings are all very good, it is still our dream to have Quality and Excellence; results explain that we need to exert more efforts to improve the implementation of the graduate school programs. In particular, the areas on extracurricular activities (x=3.22; Sd = .776) and laboratory resources (x=3.20; Sd = .721) must be given much focus for improvement [26][27][28][29][30].…”
Section: Objective #4: To Describe the Graduates' Overall Evaluation ...mentioning
confidence: 99%